Elimination of Solanum nigrum ilarvirus 1 and Apple Hammerhead Viroid from Apple Cultivars Using Antivirals Ribavirin, Rimantadine, and Zidovudine - Sedlák, Jiří; Přibylová, Jaroslava; Koloňuk, Igor; Špak, Josef; Lenz, Ondřej; Semerák, Matěj (Viruses, 2023)
Apple hammerhead viroid (AHVd) was detected in the apple cultivar 'Šampion' and in mixed infection with Solanum nigrum ilarvirus 1 (SnIV-1) in the cultivars 'Selena' and 'Jonagored Supra', using a high-throughput sequencing method. Experiments were conducted to eliminate both pathogens in apples using meristem tip cultures in combination with the antivirotics ribavirin, rimantadine, and zidovudine. Elimination of both pathogens was verified by repeated RT-PCR and qRT-PCR assays after 7-11 months. Elimination of SnIV-1 from all cultivars was successful with each of the three antivirotics at concentrations of 20, 40, and 80 mg L-1. Elimination of AHVd was also achieved, although less effectively and only with ribavirin in the concentration range of 20-160 mg L-1.
Keywords: rimantadin; Ilarvirus; Solanum nigrum; chemotherapy; apple; virus; antivirové látky; Viroids; Malus; zidovudin; Antiviral Agents; ribavirin; HTS; viroid; viroidy; Ribavirin; Zidovudine; Rimantadine